Comparative study and determinants of infection control practices of mothers of under- five children in selected health care institutions in Ibadan. - Oluwatosin, O Abimbola (International Journal of Infection Control, 2014)
Improving family and community health practices have been identified as childhood mortality reducing strategies. This cross sectional study was conducted among mothers of under-five children attending three selected Health Centers (HCs) in Ibadan.Convenient sampling method was used to select 220 mothers who provided information by means of a structured questionnaire. Data analysis was by descriptive statistics of frequency tables, ANOVA to compare mean knowledge, attitude and practice scores in the three HCs and Spearman rho’s correlation for test of relationship between variables. The mean +SD age of respondents was 29.5 + 5.7 years, 95.5% were married and most of the participants were traders. The major source of information was health talks at immunization clinics (69.1%). Respiratory tract infection was the most listed (65.9%) common childhood disease. The overall mean percent - score + (SD) for knowledge, attitude and practice of infection control were 55.9 + 15.0, 42.4 + 11.8 and 31.1 + 15.7 respectively. Mean knowledge score of 63.2 + 17.0 by participants at the university HC was significantly higher than that of participants in the other two HCs, F = 9.32, p = 0.00. Correlation showed significant relationship between knowledge and attitude p= 0.000, knowledge and practice p=0.000 as well as attitude and practice p=0.006. Only eight (3.6%) would wash their hands always after attending to the need of a sick child though 189 (85.9%) acknowledged hand washing as a strategy for infection control. Findings indicate the need to explore strategies to improve attitude and practice of mothers.